KESIAPAN PELAKSANAAN PEMBELAJARAN TATAP MUKA DI SMK NEGERI 2 TORAJA UTARA PADA MASA PANDEMI - Oce Payung Limbong; Witarsa Tambunan; Mesta Limbong (Jurnal Manajemen Pendidikan, 2021)
The purpose of this study was to determine the readiness for face-to-face learning at SMK Negeri 2 Toraja Utara. The analysis used in this study is a qualitative analysis using the subject matter approach. In order for maximum face-to-face learning readiness, school leaders must involve teachers, school committees and parents of students at the meeting to determine face-to-face learning procedures and send the results of determining face-to-face learning for parents who do not attend meetings so that learning procedures are clear so that learning readiness is maximized resulting in learning objectives can be achieved. From the results of this study it can be concluded that the readiness for face-to-face learning at SMK Negeri 2 Toraja Utara has not been maximized because at the meeting to determine the procedure for determining face-to-face learning, it was only attended by a few parents of students and there were also some teachers who were not present at the meeting. Keywords: readiness, face to face learning, pandemic